PENINGKATAN KETERAMPILAN LITERASI SAINS MELALUI PEMBELAJARAN INKUIRI TERBIMBING BERBASIS SOCIO SCIENTIFIC ISSUE (SSI) PADA MATERI STRUKTUR BUMI - Rizki Puspitasari, Tita; Bintang Ilhami, Fasih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the improvement of students' scientific literacy skills through the application of a guided inquiry learning model based on Socio-Scientific Issues (SSI) on the material of earth structure and its development. This study used a quantitative method with a pre-experimental design in the form of a one-group pretest-posttest design on 30 junior high school students. The research instrument was a scientific literacy essay test given before and after treatment. Data were analyzed using the Shapiro-Wilk normality test, paired sample t-test, and N-Gain test. The results showed an increase in students' scientific literacy skills after the implementation of guided inquiry learning based on SSI. The results of the paired sample t-test showed a significant value between the pretest and posttest results. The N-Gain analysis obtained an average of 0.59 with a moderate category. The indicator